Kamus lengkap inggris - Indonesia; Indonesia - Inggris (Bonus 50 Proverbs)/ Fatya Permta Anbiya; Rani Andriani Koswara; Yelvi Andri Z - Anbiya, Fatya Permata Rani Andriani Koswara Yelvi Andri Z (Jakarta:Penebit TransMedia, 2014)
Koleksi Referensi (Tidak Dipinjamkan)